2022
DOI: 10.1093/geront/gnac180
|View full text |Cite
|
Sign up to set email alerts
|

Third Places for Older Adults’ Social Engagement: A Scoping Review and Research Agenda

Abstract: Background and Objectives Neighbourhood places that facilitate older residents to meet and interact (third places) receive an increasing research interest as studies have consistently shown the benefits of social engagement for older adults’ health. This scoping review synthesised the findings of studies examining the role of third places in older adults’ social engagement. Research Design and Methods Searching five databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…For example, Sugiyama et al describe the importance of local community hubs as a safe space for meeting and interacting with new people, to develop one’s social network. Two key factors they identify are convenience and comfortability, both in visiting such spaces and with respect to time spent therein ( Sugiyama et al, 2022 ). In describing the results from their review and analysis of the literature over the past 25 years, Sugiyama et al (2022) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Sugiyama et al describe the importance of local community hubs as a safe space for meeting and interacting with new people, to develop one’s social network. Two key factors they identify are convenience and comfortability, both in visiting such spaces and with respect to time spent therein ( Sugiyama et al, 2022 ). In describing the results from their review and analysis of the literature over the past 25 years, Sugiyama et al (2022) .…”
Section: Discussionmentioning
confidence: 99%
“…Two key factors they identify are convenience and comfortability, both in visiting such spaces and with respect to time spent therein ( Sugiyama et al, 2022 ). In describing the results from their review and analysis of the literature over the past 25 years, Sugiyama et al (2022) . make several recommendations on how such spaces should look like; for example, lush greenery and visually arresting natural sights, in addition to facilitating opportunities for social interaction in the form of transition spaces for example, a bench in an urban park where one might strike up a conversation with another.…”
Section: Discussionmentioning
confidence: 99%
“…A previous natural experiment study in Japan also reported a lower cognitive decline risk among older adults relocated to neighborhoods with high community-level informal socializing and social participation resources [ 37 ]. Different types of neighborhood resources may have offered cognitive benefits to older adults who are cognitively intact, in part through pathways such as a high density of restaurants offering seniors a space for informal gathering; recreational facilities directly facilitating physical and social activities; and social service establishments increasing opportunities for social interaction [ 19 ] or engagement [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, they may lead to potentially null findings and limit our understanding of the pathways by which greenspace contributes to health in urban and rural contexts. A scoping review of 32 articles investigating the role of green space indeed found that the availability of local businesses, community‐use structures, and open spaces were related to the degree of social interactions 157 . Despite these few preliminary studies, the neighborhood and environmental living, working, and learning conditions in rural locales have been understudied to date in relation to ADRD, particularly in regions other than Europe, Japan, and China.…”
Section: Modifiable Factors Contributing To Adrd Burden In Rural Areasmentioning
confidence: 99%